Indigenous knowledge: Saving traditions - Singleton, Guy (Technical Centre for Agricultural and Rural Cooperation, 2008)
A long running project of the indigenous Ngalia people of Western Australia has adapted a wide variety of technologies in their fi ght to preserve their traditional knowledge and culture